ANALISIS KESEJAHTERAAN USAHA KECIL DAN MENENGAH (UKM) DI KABUPATEN JEPARA - Moch Aminnudin; Hamdi Sari Maryoni (Jurnal Ilmiah Cano Ekonomos, 2021)
This study uses quantitative and qualitative research types that try to answer the magnitude of the influence of the Small and Medium Business Welfare variable for the community with a sample of 99 respondents, showing the magnitude of R square (coefficientof determination) R square of 0.658 or 65.8%. Thus it can be concluded that the independent variable can explain 65.8% of the independent variable, while the remaining 34.2% is explained by other factors outside the simple linear regression equation model. build prosperity for the community, especially the business community in every village in Jepara Regency. This can be indicated by the magnitude of the contribution of the historical factor of 4 (four) dimensions which are used as indicators to measure how much influence the ommunity Welfare has, namely: Income, Health, Education and Social Relations